2003
DOI: 10.5794/jjoms.49.566
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of 17 cases of malignant tumors metastatic to the mouth and jaws

Abstract: Metastatic tumors of the oral region are relatively rare and comprise approximately 1 % of malignant oral neoplasms. Their prognosis is generally very poor because of systemic metastases. We clinically studied 17 cases of metastatic tumors of the oral region. Fourteen of the 17 patients were male and 3 were female. The mean age was 56.6 years. Metastases to the mandible were twice as frequent as those to the maxilla. The most common location of the metastatic lesions was the molar region of the jaws. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Consistent with the findings in this case, metastatic tumors in the oral and maxillofacial regions are frequently encountered as multiple metastases and exhibit a high fatality rate ( 22 , 23 ). A comprehensive evaluation of the primary tumor and the presence or absence of metastases is crucial in determining an effective treatment plan.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the findings in this case, metastatic tumors in the oral and maxillofacial regions are frequently encountered as multiple metastases and exhibit a high fatality rate ( 22 , 23 ). A comprehensive evaluation of the primary tumor and the presence or absence of metastases is crucial in determining an effective treatment plan.…”
Section: Discussionsupporting
confidence: 91%
“…The diagnostic criteria for metastatic tumors include the presence of a primary tumor or the absence of other tumor lesions (Tables II and III) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Additionally, The histological similarity between the primary tumor and the metastases 3…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recommended palliative treatment (e.g., surgical treatment, chemotherapy, and radiotherapy) to improve the quality of life (QOL) and to maintain the patient's comfort 7,8 . We found 54 cases of oral metastasis of PCs that were reported from 1991 to 2021 in PubMed and Google scholar 9–45 and reviewed these cases, including our case. Kaplan‐Meier survival analyses were performed to determine whether palliative treatment affected overall survival.…”
Section: Discussionmentioning
confidence: 91%
“…In our review, 41 of 54 patients received palliative treatments, and surgical treatments were common ( n = 10), followed by chemoradiotherapy ( n = 8) (Table 1). 8–44 There were no significant differences in the survival times between patients with and without palliative treatment at 6.49 and 4.36 months, according to the results of the Kaplan‐Meier test (log rank test: P = 0.437, Figure 4), which suggested that palliative treatment had no effect on survival time. Our patient was able to consume food orally using the upper denture after surgical treatment, showing that even if radical therapy cannot be administered, palliative treatment for maintaining oral function may contribute to the improvement of the QOL.…”
Section: Discussionmentioning
confidence: 95%
“…All malignant tumors can metastasize to the oral cavity, but most often the primary tumor involves the lungs, kidneys, liver, and prostate gland in male patients and mammary glands, genitals, and kidneys in female patients [ 5 ]. Metastases in the maxillofacial region and the oral cavity are often multiple and are associated with a high mortality rate [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%